Good medicine and good health-care demand good information (systems) - Winter, Alfred; Hilgers, R.-D.; Hofestädt, R.; Hübner, U.; Knaup-Gregori, Petra; Ose, C.; Schmoor, C.; Timmer, A.; Wege, D. (Methods of information in medicine, 2015)
The demand for evidence-based health informatics and benchmarking of ‘good’ information systems in health care gives an opportunity to continue reporting on recent papers in the German journal GMS Medical Informatics, Biometry and Epidemiology (MIBE) here. The publications in focus deal with a comparison of benchmarking initiatives in German-speaking countries, use of communication standards in telemonitoring scenarios, the estimation of national cancer incidence rates and modifications of parametric tests. Furthermore papers in this issue of MIM are introduced which originally have been presented at the Annual Conference of the German Society of Medical Informatics, Biometry and Epidemiology. They deal as well with evidence and evaluation of ‘good’ information systems but also with data harmonization, surveillance in obstetrics, adaptive designs and parametrical testing in statistical analysis, patient registries and signal processing.